2017
DOI: 10.1016/j.bulsci.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

On the quaternionic Monge–Ampère operator, closed positive currents and Lelong–Jensen type formula on the quaternionic space

Abstract: In this paper, we introduce the first-order differential operators d0 and d1 acting on the quaternionic version of differential forms on the flat quaternionic space H n . The behavior of d0, d1 and △ = d0d1 is very similar to ∂, ∂ and ∂∂ in several complex variables. The quaternionic Monge-Ampère operator can be defined as (△u) n and has a simple explicit expression. We define the notion of closed positive currents in the quaternionic case, and extend several results in complex pluripotential theory to the qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(89 citation statements)
references
References 28 publications
(46 reference statements)
1
87
0
1
Order By: Relevance
“…Then Alesker and Verbitsky studied the quaternionic Monge-Ampère operator on general quaternionic manifolds ( [4,16] and references therein). In Wan and Wang [18] we established an explicit expression of the quaternionic MongeAmpère operator: it can be defined as ( u) n , where the Baston operator = d 0 d 1 is the first operator of 0-Cauchy-Fueter complex:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then Alesker and Verbitsky studied the quaternionic Monge-Ampère operator on general quaternionic manifolds ( [4,16] and references therein). In Wan and Wang [18] we established an explicit expression of the quaternionic MongeAmpère operator: it can be defined as ( u) n , where the Baston operator = d 0 d 1 is the first operator of 0-Cauchy-Fueter complex:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…By introducing the quaternionic version of differential forms, we defined in Wan and Wang [18] the notions of closed positive forms and closed positive currents in the quaternionic case and our definition of closedness matches positivity well. We proved that u is a closed positive 2-current for any plurisubharmonic function u, and showed that when functions u 1 , .…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…∧ △u n = µΩ 2n for a well defined positive Radon measure µ. See [17] for the detailed information about the closed positive currents in H n .…”
Section: Preliminaries On Quaternionic Monge-ampère Measurementioning
confidence: 99%
“…Motivated by this, Wang and the author introduced in [17] ∂, ∂ and ∂∂ in several complex variables. The quaternionic Monge-Ampère operator can be defined as (△u) n and has a simple explicit expression, which is much more convenient than the definition by using Moore determinant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation